Hyperthermic intravesical chemotherapy with gemcitabine versus Bacillus Calmette–Guerin in intermediate- and high-risk non-muscle-invasive bladder cancer - Yan, Bing; Hu, Wenya; Li, Yanran; Feng, Tao; Zhu, Lei; Xu, Haifeng; Chen, Shubo; Qiao, Yuhua (Frontiers in Oncology, 2026)
BackgroundThe recurrence rate remains high in patients with intermediate- and high-risk non-muscle-invasive bladder cancer (NMIBC), and some patients may experience disease progression despite curative trans-urethral resection and adjuvant therapy.ObjectiveTo compare the outcomes of intermediate- and high-risk NMIBC patients treated with Bacillus Calmette–Guerin (BCG) versus hyperthermic intravesical chemotherapy (HIVEC) with gemcitabine (GEM).MethodsA retrospective analysis of our single-institutional, prospectively collected database from July 2018 to February 2020 was performed. Patients with intermediate- and high-risk NMIBC and treated with HIVEC/GEM or BCG were selected. The two adjuvant therapies were compared in terms of recurrence-free survival (RFS), progress-free survival (PFS), and cancer-specific survival (CSS) at 24 months. Adverse events were also assessed and compared between groups.ResultsA total of 85 patients (38 in the HIVEC/GEM group and 47 in the BCG group) were included in the study. Patients’ characteristics were comparable between groups. There were no statistically significant differences in RFS (78.0% for HIVEC/GEM versus 75.0% for BCG, p = 0.592), PFS (91.7% for HIVEC/GEM versus 94.6% for BCG, p = 0.670), and CSS at 24 months. AEs were less common with HIVEC/GEM treatment than BCG (47.37% (18/38) versus 70.20% (33/47), p = 0.033). Most AEs were mild with CTCAE grade 1-2 (42.1% (16/38) for HIVEC/GEM and 63.8% (30/47) for BCG, p = 0.046).ConclusionsAmong patients with intermediate- and high-risk NMIBC, hyperthermic intravesical chemotherapy combined with gemcitabine, compared with BCG treatment, significantly reduced the adverse events rate without compromising oncological survival outcomes. The primary limitations of this study are its small sample size and retrospective nature.